Phonics [4DVD set] : complete phonics program. (Conroe, TX : RockNLearn, Inc., 2017)
This Complete program a favorite way to boost reading and spelling skills. DVD menus allow easy access for practice and repetition. Delayed answers and the on-screen mouth let learners check their progress. Story practice and free printable worksheets reinforce skills.